LBA5 KRAS mutational status and efficacy in KEYNOTE-189: Pembrolizumab (pembro) plus chemotherapy (chemo) vs placebo plus chemo as first-line therapy for metastatic non-squamous NSCLC. (15th December 2019) - Gadgeel, S; Rodriguez-Abreu, D; Felip, E; Esteban, E; Speranza, G; Reck, M; Hui, R; Boyer, M; Garon, E B; Horinouchi, H; Cristescu, R; Aurora-Garg, D; et al.
Abstract: Background: KRAS mutations are observed in ∼25% of lung adenocarcinomas, with some studies suggesting it is a prognostic factor in NSCLC. We assessed the prevalence of KRAS mutations and their association with efficacy in an exploratory analysis of the KEYNOTE-189 study of pembrolizumab plus pemetrexed and platinum chemotherapy vs placebo plus chemotherapy as first-line therapy for metastatic non-squamous NSCLC (NCT02578680). Methods: Whole-exome sequencing (WES) was used to assess KRAS status and tumor mutational burden (TMB) in participants (pts) who had available tumor and matched-normal tissue. Descriptive analyses of the association of KRAS and KRAS G12C status with efficacy were included as part of this exploratory analysis, as was correlation between KRAS mutational status and shifts in TMB and PD-L1 expression distributions. Results: 289 (47%) of 616 pts had evaluable WES data from both tumor and normal DNA. 89 (31%) of 289 pts had KRAS mutation, including 37 (13%) G12C carriers. Pts with vs without KRAS mutations tended to have higher PD-L1 TPS (median [IQR] 30% [1-71] vs 5% [0-60]) and higher TMB (median [IQR] 204 [137-276] vs 141 [85-252] mut/exome). Outcomes of pembrolizumab plus chemotherapy and of placebo plus chemotherapy in pts with and without KRAS mutation and in KRAS G12C carriers are summarized in the table. 95% CIs were wide given the modest frequency of KRAS mutation, particularly KRAS G12C, and the 2:1 randomization that resulted in small populations for placebo plus chemotherapy. Conclusion: Based on this descriptive exploratory analysis, pembrolizumab plus pemetrexed and a platinum should be a standard first-line treatment for pts with metastatic non-squamous NSCLC regardless of KRAS mutation status. Clinical trial identification: KEYNOTE-189, NCT02578680. Editorial acknowledgement: Joanne Tomassini and Melanie Leiby, both of Merck & Co., Inc., Kenilworth, NJ, USA, for writing support. Legal entity responsible for the study: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Funding: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Disclosure: S. Gadgeel: Advisory / Consultancy: Boehringer-Ingelheim; Advisory / Consultancy: Xcovery; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Novocure; Advisory / Consultancy, Travel / Accommodation / Expenses: Genentech/Roche; Advisory / Consultancy: Takeda; Research grant / Funding (institution): Merck Sharp & Dohme; Advisory / Consultancy: Pharmamar. D. Rodriguez-Abreu: Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Roche; Honoraria (self), Speaker Bureau / Expert testimony: AstraZeneca; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: BMS; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: MSD; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Eli Lilly; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Pfizer; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Novartis. E. Felip: Advisory / Consultancy: Boehringer Ingelheim; Advisory / Consultancy: Eli Lilly; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Roche; Advisory / Consultancy, Research grant / Funding (institution): Merck Sharp & Dohme; Advisory / Consultancy: Abbvie; Honoraria (self), lecture fees: AstraZeneca; Honoraria (self), lecture fees: Bristol Myers Squibb; Honoraria (self), lecture fees: Novartis. E. Esteban: Travel / Accommodation / Expenses: Pfizer; Travel / Accommodation / Expenses: Roche; Travel / Accommodation / Expenses: AstraZeneca; Travel / Accommodation / Expenses: Novartis; Research grant / Funding (institution): MSD. G. Speranza: Research grant / Funding (institution): MSD. M. Reck: Honoraria (self), Advisory / Consultancy: Amgen; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: BMS; Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy: Celgene; Honoraria (self), Advisory / Consultancy: Merck ; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): MSD; Honoraria (self), Advisory / Consultancy: Eli LIlly; Honoraria (self), Advisory / Consultancy: Pfizer; Honoraria (self), Advisory / Consultancy: Abbvie; Honoraria (self), Advisory / Consultancy: Roche; Honoraria (self), Advisory / Consultancy: Novartis. R. Hui: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): MSD; Honoraria (self), Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: BMS; Honoraria (self), Advisory / Consultancy: Novartis; Honoraria (self), Advisory / Consultancy: Roche; Advisory / Consultancy: Eli Lilly. M. Boyer: Honoraria (self), Honoraria (institution), Research grant / Funding (institution): AstraZeneca; Honoraria (institution), Research grant / Funding (institution): MSD; Honoraria (institution): Roche; Research grant / Funding (institution): Amgen; Research grant / Funding (institution): BMS; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Beigene; Research grant / Funding (institution): Ascentage Pharma; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Roche/Genentech; Research grant / Funding (institution): Janssen. E.B. Garon: Honoraria (self): Dracen; Honoraria (self), Research grant / Funding (institution): EMD Serono; Honoraria (self), Research grant / Funding (institution): Novartis; Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): BMS; Research grant / Funding (institution): Genentech; Research grant / Funding (institution): Eli Lilly; Research grant / Funding (institution): Dynavax; Research grant / Funding (institution): Iovance; Research grant / Funding (institution): Mirati; Research grant / Funding (institution): Neon; Research grant / Funding (institution): MSD. H. Horinouchi: Honoraria (self), Advisory / Consultancy: Eli LIlly; Honoraria (self), Research grant / Funding (institution): BMS; Honoraria (self), Research grant / Funding (institution): ONO; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): MSD; Honoraria (self): Kyowa-Kirin; Honoraria (self): Taiho; Research grant / Funding (institution): Daiichi-Sankyo; Research grant / Funding (institution): Abbvie; Research grant / Funding (institution): Chugai/Roche; Research grant / Funding (institution): Genomic Health. R. Cristescu: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck Sharp & Dohme. D. Aurora-Garg: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck Sharp & Dohme. J. Lunceford: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck Sharp & Dohme. J. Kobie: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck Sharp & Dohme. M. Ayers: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck Sharp & Dohme. B. Piperdi: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck Sharp & Dohme. M.C. Pietanza: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck Sharp & Dohme. M.C. Garassino: Advisory / Consultancy, Research grant / Funding (institution): MSD; Research grant / Funding (institution): Eli Lilly; Research grant / Funding (institution): Boehringer Ingelheim; Research grant / Funding (institution): Otsuka Pharma; Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): BMS; Research grant / Funding (institution): Roche; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Celgene; Advisory / Consultancy: Incyte; Advisory / Consultancy: Takeda; Advisory / Consultancy: Inivata; Advisory / Consultancy: Takeda; Research grant / Funding (institution): Tiziana Sciences; Research grant / Funding (institution): Clovis; Research grant / Funding (institution): Merck Serono; Research grant / Funding (institution): Bayer; Advisory / Consultancy, Research grant / Funding (institution): GSK; Advisory / Consultancy: Sanofi-Aventis; Research grant / Funding (institution): Spectrum Pharmaceuticals.